2014
DOI: 10.1111/exd.12372
|View full text |Cite
|
Sign up to set email alerts
|

Role of oxidative stress and autoimmunity in onset and progression of vitiligo

Abstract: Figure S1. (a-c) Specificity of the antibody was verified in sections of paraffin-embedded HEK cells transiently transfected with human b) and , respectively. The sections were subjected to immunofluorescence; (a) HEK cells transfected with human IL-20 stained with polyclonal rabbit anti-IL-20 and detected with Alexa 488 (green); (b) HEK cells transfected with human IL-20 and stained with a preimmune serum control from the rabbit in which the polyclonal rabbit anti-IL-20 was generated and detected with Alexa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 27 publications
1
52
0
2
Order By: Relevance
“…IL1B also plays a crucial role in driving the differentiation of Th17 and Th1 cells, ultimately evoking immune response against melanocytes [71]. Our recent studies have shown decrease in regulatory T-cells, increase in CD8 + T-cells and anti-melanocyte antibody levels in GV patients which were positively correlated with disease onset and progression [72], [73].…”
Section: Discussionmentioning
confidence: 91%
“…IL1B also plays a crucial role in driving the differentiation of Th17 and Th1 cells, ultimately evoking immune response against melanocytes [71]. Our recent studies have shown decrease in regulatory T-cells, increase in CD8 + T-cells and anti-melanocyte antibody levels in GV patients which were positively correlated with disease onset and progression [72], [73].…”
Section: Discussionmentioning
confidence: 91%
“…The autoimmune theory is the best-supported one, because vitiligo may be associated with other autoimmune diseases including pernicious anemia, hyperthyroidism, Hashimoto's thyroiditis, alopecia areata and adrenocortical failure. Furthermore, histological studies have demonstrated a high frequency of cytotoxic T lymphocytes specific to melanocytic antigens in vitiligo lesions, suggesting a direct, melanocyte-specific T cell attack [9, 11, 12]. …”
Section: Discussionmentioning
confidence: 99%
“…tyrosinase related protein 1 and 2 [8][9][10][39][40][41][42][43][44], but the cellular and molecular mechanisms that are responsible for the production of autoantibodies and the ways through which these antibodies participate in skin depigmentation remain highly controversial and point of debate [11,12,[44][45][46]. Despite of these controversy, the interplay between ROS and the autoimmunity in vitiligo is understood [12,45].…”
Section: Subjectsmentioning
confidence: 99%
“…Despite of these controversy, the interplay between ROS and the autoimmunity in vitiligo is understood [12,45]. As for example, the excess production of ROS cause defective apoptosis of melanocytes, resulting in release of aberrated proteins, which can serve as autoantigens leading to autoimmunity [12,46].…”
Section: Subjectsmentioning
confidence: 99%